Spontaneous omental torsion: a case study and review of clinical challenges - Sapra, Akhilesh; Ramzi, Amjad; Sapra, Anju; Somani, Piyush; Zafar, Syed (International Surgery Journal, 2025)
Omental torsion (OT) is one among the rarest causes of abdominal pain, with very few cases reported in the literature. Its presentation is usually seen in the fourth and fifth decades of one’s life span. We report one such case, wherein a 36-year-old male presented with acute abdominal pain, particularly on the right iliac fossa (RIF), resulting in the clinical suspicion of appendicitis. Computed tomography findings were suggestive of a diagnosis of OT. Histopathology results revealed omental ischemia, thus confirming this diagnosis.